Combination Activity of Standard Antituberculosis Drugs and Extracts of Medicinal Plants Commonly Used in Traditional Treatment of Tuberculosis in Uganda - Mpeirwe, Moses; Komakech, Kevin; Sesaazi, Crispin Duncan; Ogwang, Patrick Engeu; Bazira, Joel (Advances in Infectious Diseases, 2024)
Introduction: Resistance to antituberculosis drugs and adverse drug reactions remain the leading causes of tuberculosis therapeutic failure globally. Despite the increasing acceptance of medicinal plant use in combination with conventional antituberculosis drugs in treatment of tuberculosis (TB) in Uganda, there is paucity of knowledge on their combination effect. Aim: This research aimed to determine combination activity of standard antituberculosis drugs with extracts of Zanthoxylum leprieurii Guill. & Perr. and Rubia cordifolia L., the two common antituberculosis medicinal plants in Uganda, against pansensitive (H37Rv) and multi-drug resistant (MDR) Mycobacterium tuberculosis strains. Materials and Methods: Two reference MTB strains (H37Rv and MDR strain) were inoculated on Middlebrook 7H11 medium containing a combination of standard antituberculosis drugs and methanol extracts of Z. leprieurii and R. cordifolia at varying concentrations. The number of colonies on the plates was observed and counted weekly for up to 8 weeks. In vitro combination activity was determined using proportion method. Mean percentage inhibition was calculated for the reduction of number of colonies on drug-extract combination medium in relation to drug-extract-free control medium. Results: Drug-extract combinations showed good combination activity against Mycobacterium tuberculosis strains when compared with individual standard anti-TB drugs. This was more exhibited against MDR strain. There was however a reduction in percentage inhibition when extracts were combined with ethambutol and streptomycin against H37Rv strain. Conclusions: Zanthoxylum leprieurii and Rubia cordifolia in combination with standard anti-TB drugs exhibited increased in vitro activity against Mycobacterium tuberculosis, especially MDRTB strain. This justifies the local use of these plants in traditional treatment of tuberculosis especially in resistant cases in Uganda.
Keywords: Combination Activity; Medicinal Plants; Zanthoxylum leprieurii; Rubia cordifolia; Standard Antituberculosis Drugs